Analysis of the Classical Management Approach, a Descriptive View - Robinson Andres Vasquez Lujan; Orlando Carmelo Castellanos Polo (MultiTech Publisher, 2023)
An approach to the management approach is made, starting from the classical or traditional theory of Henry Fayol. Theory that establishes the functions and principles of management applied to organizations. Analyze the approaches to management, starting from the classical theory also known as